Pengaruh Kepuasan Kerja Dan Motivasi Kerja Terhadap Produktivitas Kerja Karyawan Bagian Produksi Pt.Sumber Sawit Sejahtera Pelalawan - Triningsih, Febri; Hendriani, Susi; Pramadewi, Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aim to know how influence Satisfaction Work variable and Motivation work by simultan and parsial of performance employees to department Production PT. Sumber Sawit Sejahtera Pelalawan. As for becoming population in this research is counted 50 people employees PT. Sumber Sawit Sejahtera Pelalawan. Used data by analysis is descriptive,despitefully also use quantitative analysis that is using double linear regression constructively SPSS version program 18. From result of examination which have been simultan regressi test (uji F) indicate that Satisfaction Work And Motivaiton Work by simultan have an effect on signifikan to employees performance.Result of test parsial (uji T) indicating that satisfaction variable work and motivation work by parsial have an effect on significan to employees performance.Keywords : Satisfaction,motivation, and productivity work.